Adrenergic response to maximum exercise of trained road syclists - Janikowska, G.; Kochanska-Dziurowicz, A.; Zebrowska, A.; Bijak, A.; Kimsa, M. (Journal of Human Kinetics, 2014)
The aim of this study was to evaluate adrenergic responses in the peripheral blood of trained road cyclists at rest, at maximal intensity of incremental bicycle exercise test, and during 15 minutes of recovery, as well as the relationship between them. Competitive male road cyclists, in the pre-competitive phase of a season, mean age 21.7 ± 6.4 years, and BMI 20.7 ± 0.8 kg·m-2, performed an incremental test on a bicycle ergometer with unloaded cycling for 5 min, then increased the load to 40 W every 3 min, up to maximal exercise intensity. The plasma catecholamine concentrations (epinephrine, norepinephrine) and oxygen uptake were estimated. The expression of 132 genes related to the adrenergic system in leukocytes was measured. A statistically significant increase in plasma epinephrine concentration (p < 0.01) was observed in response to exercise. The mean of maximal oxygen uptake was 65.7 ± 5.5 ml·kg-1·min-1. The RGS2 gene expression was highest regardless of the test phase for all athletes. The effort had a statistically significant influence on ADRB2 and RAB2A expression. In addition, the RAB2A, ADM and HSPB1 expression level increased during recovery. We can conclude that plasma epinephrine concentration and genes related to the adrenergic system such as ADM, ADRB2, CCL3, GPRASP1, HSPB1, RAB2A, RGS2 and ROCK1 seem to have an influence on the response to high-intensity exercise in trained cyclists.